Left ventricular global function index: diagnostic and prognostic value in cardiovascular diseases - A. Yu. Kapustina; M. N. Alekhin (Российский кардиологический журнал, 2023)
Left ventricular global function index (LVGFI) is a novel indicator for assessing LV function, considering the main components of cardiac remodeling, obtained using magnetic resonance imaging and echocardiography. Works with the assessment of normal LVGFI values were analyzed. The review provides data on the diagnostic and prognostic efficacy of LVGFI in various cardiovascular diseases, such as heart failure, myocardial infarction, cardiomyopathy, and amyloidosis. Examples of LVGFI calculation in healthy patients and in those with listed pathologies are also presented.